2005
DOI: 10.1068/p5033
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Balance of Color Triads in the Abstract Art of Piet Mondrian

Abstract: We examined the interactive contribution of the color and size of the three areas occupied by the primary colors red, yellow, and blue in adaptations of abstract compositions by Mondrian to the perceived weight of the areas and the location of the balance centers of the compositions. Thirty-six art stimuli were created by experimentally changing the colors in the three areas of six original works so that the resulting five variations and the original constituted the six possible spatial arrangements of the thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
49
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 17 publications
(28 reference statements)
1
49
0
Order By: Relevance
“…There exists a body of work endeavouring to understand visual balance and its relation with symmetry [4] about vertical [5][6][7] and horizontal [7] axes, content of the scene [8], color contrast [9,10], and styles in abstract and representational artworks [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…There exists a body of work endeavouring to understand visual balance and its relation with symmetry [4] about vertical [5][6][7] and horizontal [7] axes, content of the scene [8], color contrast [9,10], and styles in abstract and representational artworks [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Locher et al (2005) examined the perception of balance in six abstract paintings by Piet Mondrian together with variations of those paintings in which the colors (red, blue, and yellow) were interchanged. They found that Mondrian's originals were all judged to be balanced near the center, whereas the manipulations were generally perceived as less well balanced.…”
Section: Introductionmentioning
confidence: 99%
“…Various investigations linked balance to composition “correctness”, “rightness”, or “goodness”, comparing original compositions with perturbed versions, producing theories based on aesthetic experience and viewers' art expertise (Locher 1996, 2003; Locher and Stappers 2002; Locher et al 1998, 1999, 2005, 2007; McManus and Kitson 1995; Nodine et al 1993). The directionality of elements and their implicit dynamic quality contribute to their weight and composition balance (Locher and Stappers 2002; Locher et al 1998; Mead and McLaughlin 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The directionality of elements and their implicit dynamic quality contribute to their weight and composition balance (Locher and Stappers 2002; Locher et al 1998; Mead and McLaughlin 1992). Studies suggest that both art-trained and novice viewers rapidly achieve complex global impressions of artwork gist including balance perception (Locher and Stappers 2002; Locher et al 1996, 2007; McManus et al 1985), perhaps within 100 ms, though these studies did not employ methods to isolate early processing from later cognitive processing.…”
Section: Introductionmentioning
confidence: 99%